2017
DOI: 10.4081/aiua.2017.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Five-year prospective study on cardiovascular events, in patients with erectile dysfunction and hypotestosterone

Abstract: Objective: Testosterone levels play a role in cardiac and vascular pathology. In the present study we investigated the prognostic significance of this hormone for cardiovascular outcome, in a 5-year follow-up. Materials and methods: Our cohort included 802 adult subjects, from 40 to 80 years. Patients were excluded if they had a past history of peripheral or coronary artery disease, and revascularization. A blood sample was drawn to valuate testosterone level, and we considered normal testosterone levels 300 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Recent studies support benefits of TRT in aged men (>60) including for cardiovascular and cerebrovascular disease [6, 10-12]. Low T, even within the reference range, is associated with an increased risk of ischemic stroke [7, 9, 59-61], and in some studies, TRT reduced risk [11, 12]. Nevertheless, others found that initiation of TRT could increase the risk of major cardiovascular events, including stroke [59, 62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies support benefits of TRT in aged men (>60) including for cardiovascular and cerebrovascular disease [6, 10-12]. Low T, even within the reference range, is associated with an increased risk of ischemic stroke [7, 9, 59-61], and in some studies, TRT reduced risk [11, 12]. Nevertheless, others found that initiation of TRT could increase the risk of major cardiovascular events, including stroke [59, 62].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that low T levels are associated with cardiovascular disease, including stroke [7][8][9], the health effects of TRT are less clear. Most recent longitudinal studies support the benefits of TRT for cardiovascular and cerebrovascular disease risk [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Dyslipidemia is frequently associated with overweight, obesity, and a broad spectrum of cardio‐metabolic disorders, which pose major public health concerns because they reduce an individual's productive years of life and cause early mortality. [ 2 ] Reduction in serum lipid levels is an important measure to control dyslipidemia and its associated complications, such as acute myocardial infarction and systemic arterial hypertension induced by atherosclerotic disease. [ 3 ] Therefore, several studies have expounded the use of potentially hypolipidemic substances as a therapeutic strategy for treating dyslipidemia and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual male dysfunction is an extremely common condition that manifests itself with erectile disorder (ED) and premature ejaculation (EP) (1), often present at the same time. In everyday clinical practice, both pathologies require a multidisciplinary approach in the diagnostic phase and in the therapeutic management (2,3) due to their multifactorial genesis, such as psychological factors and endothelial dysfunction. Female sexual dysfunctions are understudied, despite the incidence being alarmingly high: in a 30 years ago study, 76% of women were living with some symptoms of sexual dysfunction (4), while more recent literature suggest that prevalence is around 43% (5).…”
Section: Introductionmentioning
confidence: 99%